PERALIHAN HAK MILIK ATAS TANAH YANG BERASAL DARI WARISAN - Slamet, Amin (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2020)
The purpose of this research is: First, to find out the implementation of the transfer of ownership of the inherited land in Samarinda. Second, to find out the inhibiting factors in the registration of the transfer of title to inherited land in Samarinda. To find out the purpose above, then determined the research method is The Qualitative Descriptive Method, with sampling techniques by purposive sampling. Data collection techniques such as interviews with observations and study documents relevant to the problem under study.Therefore it is hoped that the National Land Agency as the only body that regulates land in Indonesia is expected to be able to better socialize land regulations so that people can better understand the importance of registering land rights transfers using deeds to provide legal certainty and protection for right holders. as well as the main purpose of land registration itself.Keywords: Land Ownership, Inheritance